ACUTE TOXICOLOGICAL INVESTIGATION OF POLYETHYLENE GLYCOL DERIVATIZED FOURTH AND FIFTH GENERATION POLY (PROPYLENEIMINE) DENDRIMERS - DWIVEDI, NITIN; PARMAR, DUSHYANT KUMAR; KESHARWANI, PRASHANT; SHAH, JIGNA (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the present study leads a comparative assessment of the toxicological profile of PEGylated fourth and fifth-generation poly (propylene imine) dendrimers (PPI). Methods: 4.0G and 5.0G generations of PPI dendrimer were synthesized and PEGylated with Mono polyethylene glycol 5000 (MPEG-5000). Each PEGylated 4.0G and 5.0G dendrimeric generation were administered in three different doses: 2.5 mg/kg, 25 mg/kg and 250 mg/kg (i.e., low, intermediate and high dose) to wister rats. After the dose administration, the blood and tissue samples of wister rats were collected after 24 h and 15 d after. All the collected samples were proceeded for hematological, biochemical and histopathological studies. Results: After 24 h of (250 mg/kg) dose administration PEGylated 5.0G PPI dendrimer the RBC count, hemoglobin content and WBC count were found 7.873±0.129 mill/cmm, 13.833±0.491g/dl and 9033.33±2384.906 mill/cmm, while PEGylated 4.0G PPI dendrimer indicated RBC count, hemoglobin content and WBC count 8.733±0.239 mill/cmm, 14.033±0.12 g/dl and 9666.667±2567.316 mill/cmm, in blood samples as compare to RBC count 9.346±0.037 mill/cmm, hemoglobin content 15.35±0.15 g/dl and WBC count 8500±286.675 mill/cmm of the animals of normal control group. Thus there are no remarkable changes (p>0.05) in RBC count, hemoglobin content and other hematological profile after 24 h in comparison of normal control group of animals. Similarily insignificant changes (p>0.05) in serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), lactate dehydrogenase (LDH) and sections of different organs indicate inoffensive nature of both generations of PEGylated 4.0G and 5.0 G PPI dendrimers. Conclusion: It can be concluded that fifth-generation PPI dendrimers are more suitable as compared to fourth generation of PPI dendrimer, while both dendrimers are not generating any severe toxicity.